2013
DOI: 10.1038/mp.2013.120
|View full text |Cite|
|
Sign up to set email alerts
|

Playing Super Mario induces structural brain plasticity: gray matter changes resulting from training with a commercial video game

Abstract: Video gaming is a highly pervasive activity, providing a multitude of complex cognitive and motor demands. Gaming can be seen as an intense training of several skills. Associated cerebral structural plasticity induced has not been investigated so far. Comparing a control with a video gaming training group that was trained for 2 months for at least 30 min per day with a platformer game, we found significant gray matter (GM) increase in right hippocampal formation (HC), right dorsolateral prefrontal cortex (DLPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
267
3
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(293 citation statements)
references
References 64 publications
10
267
3
13
Order By: Relevance
“…There were no significant correlations between the two measures of reasoning nor with the perception of emotions, which at first seemed to contradict previous studies on cognitive development related to playing frequency (Feng et al, 2007;Kühn et al, 2014;McDermott et al, 2014;Suziedelyte, 2015). However, by examining the correlations with the preference for reasoning games, these have proved to be significant.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…There were no significant correlations between the two measures of reasoning nor with the perception of emotions, which at first seemed to contradict previous studies on cognitive development related to playing frequency (Feng et al, 2007;Kühn et al, 2014;McDermott et al, 2014;Suziedelyte, 2015). However, by examining the correlations with the preference for reasoning games, these have proved to be significant.…”
Section: Discussioncontrasting
confidence: 83%
“…Research shows that certain types of video games are related to better spatial reasoning (Feng, Spence & Pratt, 2007), faster processing speed, and higher short-term visual memory (McDermott, Bavelier & Green, 2014), higher abstract reasoning, and problem-solving (Suziedelyte, 2015), among others. Literature suggests that video games can train neurological development, as in the research conducted by Kühn, Gleich, Lorenz, Lindenberger, & Gallinat (2014). The authors compared two groups: a control group with one that trained for two months in a platform game, and the results indicate a significant increase of brain matter in areas responsible for spatial location, planning, working memory, and motor performance.…”
Section: Introductionmentioning
confidence: 96%
“…For example, it has been found that taxi drivers' brains have developed in the area of navigation ability [84] and musicians' brains develop differently [85]. Very recently it has been noticed that playing games, for example Super Mario, changes the players' brains as well [86]. It has been suggested that gaming or gamers (due to the differences in their brains) could be used to solve problems of the modern world.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers at the Max Planck Institute conducted the research on the effect of video games on the human brain and realized that it had been no change in the brains of some participating volunteers through the MRI technique [48].…”
Section: Discussionmentioning
confidence: 99%